Creative Mechanisms of online Teaching in The Time of Coronavirus - Abu Adel, Mohammed Ahmed (Journal of Educational and Psychological Sciences, 2020)
In regarding to high education, most world countries have paused its universities in order to avoid spreading coronavirus, then they have been forced to follow distance education; but the education system has faced many problematic questions, such as: How to guarantee integrity and objectivity of exam while students have been examining at their homes? How can faculty control their electronic classes, knowing they have not enough experience in this sort of teaching?Because of that this paper suggests “Creative Mechanisms of online Learning in The Time of Coronavirus” according to an inductive descriptive approach; because the paper studies practical experiences.This paper answered the above two questions in light to the most modern technology techniques of Online Learning. Universities have to follow some necessary conditions to overcome these new issues, such as: qualifying all instructors with technology knowledge in order to manage their lectures proficiently, and providing some additional equipment for Online Exams, that students perform in their homes due to policy of the curfew and quarantine and this mechanism could be important and demanded requirement for virtual universities, who want to make a quantum leap in the distance education.Here are the most important results of the research; is to propose an innovative strategy that aspires to bypass the problem of controlling electronic observation for students who test in their homes, and looks forward to electronic tests exceeding traditional tests, in achieving the highest standards of objectivity and scientific integrity. And Developing the motivation of faculty members and creating motivation for them by enhancing the importance of distance education, especially in light of force majeure of this kind, and the need for the instructor to be flexible in changing his old method; to follow global changes and developments in the field of education, finally to make student, not the teacher, in the center of the educational process, by developing students ’self-learning skills, and focusing more on strengthening higher-order thinking skills, that students have research skills to find information, not passively receiving it, and critical thinking skills to convince and process information, no for memorizing them only.
Keywords: Distance education; invigilation of online exams; E-learning; Education development